Transcriptional activation of Proteasome 26S non-ATPase subunit 7 by forkhead box P3 participates in gastric cancer cell proliferation and apoptosis. Issue 2 (1st February 2022) - Xu, Yujie; Wang, Dingmao; Zhao, Guodong
ABSTRACT: Proteasome 26S non-ATPase subunit 7 (PSMD7) and forkhead box P3 (FOXP3) have been found to be both upregulated in gastric cancer tissues. FOXP3 was also predicted to have binding sites on PSMD7 promoter. Thus, this study investigated the relationship between PSMD7 and FOXP3 and their roles in gastric cancer. Bioinformatic databases predicted PSMD7 expression in non-cancerous gastric tissue and gastric cancer tissue, as well as the correlation between PSMD7 and the overall/disease free survival. PSMD7 expression in non-cancerous gastric tissue or cells and gastric cancer tissue or cells was detected by qPCR and Western blot. After PSMD7 downregulation by siRNA interference, cell viability, colony-forming capacity and cell apoptosis were analyzed with cell counting kit-8 assay, colony formation assay and terminal deoxynucleotidyl transferasemediated dUTP nick end-labeling. Proliferation and apoptosis markers were assayed by qPCR and Western blot. Dual-luciferase reporter and chromatin immunoprecipitation assays were performed to look at the binding relationship between FOXP3 and PSMD7 promoter. Cell proliferation and apoptosis were examined again after co-transfection of PSMD7 siRNA plasmid and FOXP3 overexpression plasmid. PSMD7 expression was much higher in gastric cancer tissue and cell lines. Interference with PSMD7 decreased gastric cancer cell viability, inhibited their proliferation and colony formation and promoted cell apoptosis. FOXP3 was found to bind to PSMD7 promoter and activate PSMD7 expression. Overexpression of FOXP3 could rescue the effects of PSMD7 knockdown on gastric cancer cells. PSMD7 is involved in the proliferation and apoptosis of gastric cancer cells and can be transcriptionally regulated by FOXP3.